Ocular Side Effects of Oxybutynin and Other Oral Anticholinergics Used In the Management of Overactive Bladder Syndrome: A Review. - Borgman, Christopher J. (Optometry & Visual Performance, 2016)
Oxybutynin and other oral anticholinergic medications are used in the treatment of patients with overactive bladder syndrome. However, side effects including blurred vision can occur through an extension of this same therapeutic effect. The most common ocular side effects of oral anticholinergics are reduced lacrimation (leading to ocular surface dryness) and cycloplegia (leading to accommodative deficiencies). The oral anticholinergic with the highest likelihood of causing these side effects is oxybutynin as it most easily crosses the blood-brain barrier. Eye care providers are likely to encounter patients on these types of medications and should be aware of possible ocular complications from this class of drugs. A review of this class of medications and their respective side effects is presented here.